2014
DOI: 10.1177/0003319714540319
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Severity of Asymptomatic Coronary and Carotid Artery Disease in Patients With Abdominal Aortic Aneurysm

Abstract: We evaluated the prevalence and severity of occult coronary artery disease (CAD) and cerebrovascular disease (CeVD) in patients with abdominal aortic aneurysm (AAA). We studied 100 consecutive patients with no history of CAD, normal electrocardiogram, normal systolic function, and no angina or dyspnea. All patients underwent carotid Doppler study and invasive coronary angiography. Significant CAD was observed in 61% of patients. In all, 51% of patients with significant CAD showed either left main (n = 7), 3-ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…Because elective open surgical aneurysm repair is considered high-risk surgery, when AAA and symptomatic CAD are detected, coronary artery revascularization (PCI or CABG) should be performed before AAA open repair [30]. However, the prevalence of asymptomatic, significant CAD in patients with AAA was found to be as high as 61% and, moreover, 31% of these patients fulfilled indications for coronary revascularization [31]. There is, therefore, a significant group of patients with asymptomatic but severe CAD that do not undergo coronary artery evaluation and necessary revascularization before high-risk AAA surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Because elective open surgical aneurysm repair is considered high-risk surgery, when AAA and symptomatic CAD are detected, coronary artery revascularization (PCI or CABG) should be performed before AAA open repair [30]. However, the prevalence of asymptomatic, significant CAD in patients with AAA was found to be as high as 61% and, moreover, 31% of these patients fulfilled indications for coronary revascularization [31]. There is, therefore, a significant group of patients with asymptomatic but severe CAD that do not undergo coronary artery evaluation and necessary revascularization before high-risk AAA surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The association between AAAs and carotid artery stenosis, 2 5 ischemic heart disease, 6,7 or coronary artery stenosis 8 10 is well documented. Abdominal aortic aneurysms share the same vascular risk factors with these diseases (eg, smoking, hyperlipidemia, and hypertension).…”
Section: Abdominal Aortic Aneurysms and Vascular Disease In Other Artmentioning
confidence: 99%
“…The presence of AAA is considered an equivalent risk factor as CAD [ 10 ]. It has been shown that patients affected by AAAs of any size have a risk of major cardiovascular events (MACE, including cardiovascular death or non-fatal acute myocardial infarction [MI]) that is greater than 20% at 10 years, with an additional risk of aneurysm rupture [ 11 , 12 ]. This high risk of MACE is mainly attributed to the presence of coronary and vascular disease, mostly asymptomatic [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%